(untitled) (Cultura Económica, 2018)
This paper studies the perception that Argentine society has of the business people, and questions the differences between the roles of company managers, based on the understanding that there are asymmetries in the perception that the population has of them, which then is translated to their image and its consequent decoupling with its functions in the productive scheme. The perception of the Government’s role in economic management is also analyzed. Finally, we observe how this confluence of perceptions generates a gap between what society deems right and the role that entrepreneurs should play in order to satisfy the demands that the public itself asks of the economic system.